The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s10545-016-9974-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with pentosan polysulphate in patients with MPS I: results from an open label, randomized, monocentric phase II study

Abstract: Current treatment options for MPS I have limited effects on some organs, including the skeletal system. In MPS animal models pentosan polysulphate (PPS) reduces the concentrations of glycosaminoglycans (GAGs) in tissues and body fluids and improves cartilaginous and osseous pathologies. The goals of this study were to investigate primarily the safety and secondary the clinical effects, concerning mobility and pain, of PPS treatment in MPS I patients. Four MPS I-Hurler-Scheie/-Scheie patients aged 35.6 ± 6.4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 19 publications
5
36
0
Order By: Relevance
“…Many other compounds (e.g. the antiinflammatory drug pentosan polysulfate for treating mucopolysaccharidoses, or arimoclomol, a small‐molecule inducer of the heat shock protein for NPC) have been developed and will be or are already applied in clinical trials. Based on positive effects in animal models, cyclodextrin, a cyclic oligosaccharide, was used as an experimental drug in patients with NPC, although its mechanism of action is not yet fully understood.…”
Section: Other Novel Therapiesmentioning
confidence: 99%
“…Many other compounds (e.g. the antiinflammatory drug pentosan polysulfate for treating mucopolysaccharidoses, or arimoclomol, a small‐molecule inducer of the heat shock protein for NPC) have been developed and will be or are already applied in clinical trials. Based on positive effects in animal models, cyclodextrin, a cyclic oligosaccharide, was used as an experimental drug in patients with NPC, although its mechanism of action is not yet fully understood.…”
Section: Other Novel Therapiesmentioning
confidence: 99%
“…Currently, the mechanism of how PPS leads to GAG reduction in MPS is unknown, but this was observed in multiple animal model studies and in multiple tissues. Furthermore, Hennermann et al demonstrated the safety of PPS in four adult MPS I patients and showed a reduction in urinary GAGs and some clinical improvements over a six month study period [57]. Each of these patients had received ERT for over one year prior to PPS and was maintained on ERT during the six-month study.…”
Section: Introductionmentioning
confidence: 99%
“…Immunomodulating or immunosuppressive therapies are presently applied to decrease allergic reactions . Immunomodulation has been reported in patients with Pompe disease and Gaucher's disease, with variable success, and temporary depletion of B cells (anti‐CD20) has been mostly used . However, only bone marrow transplantation in patients with mucopolysaccharidosis type I (another type of LSD) resulted in a decrease in antibody formation .…”
Section: Introductionmentioning
confidence: 99%
“…Although effective for an umber of LSDs, substantial problems and limitations are caused by the raising of antibodies upon ERT.ERT can trigger the formation of specific IgE antibodies, which may be associated with allergicr eactions ranging from mild symptomst oa naphylactics hock. [5][6][7][8][9] Moreover,E RT can result in the productiono fn eutralizing IgG antibodies that bind to the infused enzymes and might impair or even diminish the clinical effectiveness of ERT. [6] The emergence of neutralizinga nti-aGal-A antibodies in FD patients treated with agalsidase-a or agalsidase-b has been reported in severals tudies.…”
mentioning
confidence: 99%
See 1 more Smart Citation